Process for refining and safe closed filling of electronic grade chlorosilanes

CN122977387APending Publication Date: 2026-10-27SUZHOUJIAJIE FLUID TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611407027.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2026-07-13
Filing Date
2026-09-11
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

多级精馏通过增加理论塔板数和回流比来强化分离,能够去除沸点差异较大的金属氯化物,但对于硼磷缔合物,由于相对挥发度趋近于1,精馏推动力严重不足,即使采用20块以上理论塔板及10:1的回流比,产品中硼磷含量仍维持在50 ppb级别,无法满足先进制程要求,且高回流比带来再沸器和冷凝器负荷的成倍增加,导致能耗和设备投资大幅上升

Benefits of technology

[0023](1)本发明提供了一种电子级氯硅烷精制与密闭安全充装工艺,采用精馏塔、侧线抽出、固定床吸附与变温再生一体化的工艺流程,精馏塔利用组分间沸点差异将体系中沸点相差较大的轻组分预先脱除,使得进入吸附柱的物料中硼磷杂质浓度降至较低水平,该负荷分配策略使得吸附柱仅需针对残留的硼磷缔合物进行深度捕获,避免吸附剂直接处理高浓度杂质物料而导致的快速穿透,精馏预处理降低了吸附柱的入口杂质负荷,吸附柱的穿透周期得以有效延长,再生频率相应降低,装置连续运行时间增加,同时精馏塔无需采用过高回流比即可完成预分离任务,再沸器和冷凝器的热负荷控制在合理水平,设备尺寸和投资成本得以优化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977387A_ABST
    Figure CN122977387A_ABST
Patent Text Reader

Abstract

The application discloses a kind of electronic grade chlorosilane refining and closed safe filling process, it is related to high-purity electronic material preparation field, the application is directed to the problem that trace boron, phosphorus impurity is difficult to remove in depth in electronic grade trichlorosilane refining process, using the integrated process of rectification preseparation, side line extraction, low-temperature fixed bed adsorption and temperature swing regeneration coupling, through the load distribution cooperation of rectification and adsorption and the heat cycle cooperation of low-temperature adsorption and high-temperature regeneration, the service life of adsorbent can be significantly prolonged, the energy consumption and equipment investment of rectification operation can be effectively reduced, so that it realizes the efficient deep removal of boron, phosphorus impurity, the purity of product meets the strict requirements of advanced semiconductor process to electronic grade polysilicon precursor, the whole process is carried out under closed inert gas protection, and has good industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-purity electronic chemical materials preparation technology for semiconductor manufacturing, and particularly to an electronic-grade chlorosilane refining and sealed safety filling process. Background Technology

[0002] As integrated circuit manufacturing processes continue to advance towards the nanoscale, the purity requirements for electronic-grade polysilicon are also increasing. Trichlorosilane, as the most crucial precursor raw material for producing high-purity polysilicon, directly determines the quality grade of the final polysilicon product based on its intrinsic purity. However, trichlorosilane inevitably introduces various metallic and non-metallic impurities during industrial production. Among these, boron and phosphorus, due to their extremely similar solid solubility and segregation coefficients in silicon crystals, are the most difficult and potentially fatal impurities to remove from polysilicon products.

[0003] Boron impurities in industrial trichlorosilane primarily originate from the chlorination of boron in the raw material, existing as boron trichloride (boiling point 12.5℃); phosphorus impurities originate from the chlorination of phosphorus components, existing as phosphorus trichloride (boiling point 76.1℃). Although their boiling points differ somewhat from those of trichlorosilane, the actual system is far from an ideal solution. Both boron trichloride and phosphorus trichloride molecules can undergo intermolecular association with trichlorosilane molecules, generating various associated species. The apparent boiling points of these associated species in gas-liquid equilibrium approach those of the main component, and azeotropic phenomena may even occur, making it impossible to effectively separate these impurities using distillation operations designed based on ideal conditions.

[0004] To address the aforementioned separation challenges, existing technologies primarily employ two approaches. Multistage distillation enhances separation by increasing the number of theoretical plates and the reflux ratio, effectively removing metal chlorides with significant boiling point differences. However, for boron-phosphorus conjugates, the relative volatility approaches 1, resulting in insufficient distillation driving force. Even with more than 20 theoretical plates and a 10:1 reflux ratio, the boron-phosphorus content in the product remains at around 50 ppb, failing to meet advanced process requirements. Furthermore, the high reflux ratio leads to a substantial increase in the load on reboilers and condensers, resulting in a significant rise in energy consumption and equipment investment. Adsorption utilizes the active sites of solid adsorbents to selectively capture boron-phosphorus molecules. While possessing a certain removal capacity, the dynamic adsorption capacity of the adsorbent is limited, resulting in a short effective working cycle, requiring frequent regeneration and switching, and complex operation. Simultaneously, the exothermic adsorption effect can easily cause localized temperature rises in the bed, affecting the adsorption performance and mechanical stability of the adsorbent, and posing potential safety hazards to the unit's operation. Summary of the Invention

[0005] This invention overcomes the shortcomings of the prior art and provides an electronic-grade chlorosilane refining and closed-loop safe filling process. After pre-separating light and heavy impurities in a distillation column, the fraction enriched with boron-phosphorus compounds is drawn from the side stream, cooled, and then subjected to low-temperature adsorption. A dual-tower alternating temperature regeneration method is used to maintain continuous production, so as to achieve the purpose of deep removal of boron-phosphorus impurities with low energy consumption.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The present invention provides an electronic-grade chlorosilane refining and sealed safety filling process, comprising the following steps:

[0007] Trichlorosilane feedstock is continuously fed into a distillation column for distillation separation. The light component is collected from the top of the column, the heavy component is collected from the bottom of the column, and the trichlorosilane material rich in boron and phosphorus impurities is collected from the side stream above the feed plate of the distillation column.

[0008] The material collected from the side stream is pre-cooled by a heat exchanger and then fed into a fixed-bed adsorption column filled with a composite adsorbent for low-temperature adsorption to remove boron and phosphorus impurities. The composite adsorbent includes a modified X-type molecular sieve and hydroxylated multi-walled carbon nanotubes. The modified X-type molecular sieve is an X-type molecular sieve loaded with transition metal oxides.

[0009] The adsorption-purified trichlorosilane material is returned to the reflux system of the distillation column or collected as a product.

[0010] After adsorption saturation, the adsorption column is switched to the regeneration system. High-purity carrier gas is used for temperature-variable purging and regeneration under high temperature conditions. After regeneration, it is switched back to the adsorption state. The adsorption column adopts dual-tower or multi-tower alternating operation to achieve continuous production.

[0011] The process is carried out in a closed system, and inert gas protection is used throughout the distillation, adsorption and filling processes.

[0012] In a preferred embodiment of the present invention, the distillation column has ≥30 theoretical plates, an operating pressure of 0.30-0.40 MPa, a reflux ratio of 6-12:1, a top temperature of 30-36 ℃, and a bottom temperature of 80-95 ℃; the side stream is located at the 15th-25th theoretical plate of the distillation column, and the side stream amount accounts for 3-10 wt% of the total feed.

[0013] In a preferred embodiment of the present invention, the side-stream sampled material is pre-cooled to -20°C to -10°C via a heat exchanger before entering the adsorption column; the operating pressure of the adsorption column is 0.25-0.35 MPa, and the material space velocity is 0.3-1.5 h⁻¹. -1 The adsorption temperature is -20 ℃ to -10 ℃.

[0014] In a preferred embodiment of the present invention, the mass ratio of modified X-type molecular sieve to hydroxylated multi-walled carbon nanotubes in the composite adsorbent is 5-9:1-5, and the loading of transition metal oxide in the modified X-type molecular sieve is 1-10 wt%, wherein the transition metal oxide is selected from one of NiO, CuO, and ZnO.

[0015] In a preferred embodiment of the present invention, the matrix of the modified X-type molecular sieve is a 13X-type molecular sieve with a Si / Al molar ratio of 2.0-3.0 and a specific surface area ≥600 m². 2 / g, with a pore size of 0.7-1.2 nm; the modified X-type molecular sieve, after being impregnated with a transition metal oxide in equal volume, is calcined at 400-600 ℃ for 2-6 h, and its specific surface area is ≥600 m². 2 / g.

[0016] In a preferred embodiment of the present invention, the hydroxylated multi-walled carbon nanotubes are obtained by multi-walled carbon nanotubes through mixed acid oxidation treatment, and the hydroxyl content is 2.0-5.0 mmol / g; the hydroxylated multi-walled carbon nanotubes are further modified with amino functionalization by a silane coupling agent, wherein the silane coupling agent is γ-aminopropyltriethoxysilane, and the amount used is 5-20% of the mass of the carbon nanotubes.

[0017] In a preferred embodiment of the present invention, the method for forming the composite adsorbent is as follows: after mixing modified X-type molecular sieve and hydroxylated multi-walled carbon nanotubes, a binder is added, and the mixture is mixed, extruded, dried, and calcined to obtain the finished adsorbent; the binder is one of silica sol and alumina sol; based on solids, the amount of binder is 3-10% of the total mass of the adsorbent, the drying temperature is 80-150 ℃, the calcination temperature is 400-600 ℃, and the calcination atmosphere is an inert atmosphere.

[0018] In a preferred embodiment of the present invention, the regeneration carrier gas in the regeneration system is hydrogen, and the regeneration carrier gas flow rate is 0.2-0.8 m³ / s. 3 The regeneration temperature is 150-180 ℃, and the regeneration pressure is 0.10-0.30 MPa. The heating stage of the variable temperature purge regeneration is 1-3 h, the constant temperature purge stage is 1-2.5 h, the cooling stage is 1-3 h, and the total regeneration cycle is 4-8 h.

[0019] In a preferred embodiment of the present invention, the single-tower adsorption cycle is 48-96 h, the height-to-diameter ratio of the adsorption column is 3-8:1, and the specific surface area of ​​the composite adsorbent packed inside the adsorption column is ≥600 m². 2 / g, crushing strength ≥50 N / cm, bulk density 0.6-0.8 g / cm³ 3The adsorbent has an adsorption capacity of ≥2.0 mg / g for boron and ≥1.8 mg / g for phosphorus under dynamic conditions.

[0020] In a preferred embodiment of the present invention, the refined trichlorosilane product produced by the process has a boron content ≤0.08 ppb and a phosphorus content ≤0.10 ppb.

[0021] The closed-loop safety filling process includes: filtering the refined trichlorosilane product through a precision filter under inert gas protection, and then filling it into a stainless steel container that has been replaced with high-purity inert gas and vacuum treated using a closed-loop filling system. The filling volume is controlled by a mass flow meter throughout the filling process. The filling system is equipped with a pressure interlock shut-off and leakage detection device. After filling is completed, the container valve is sealed and leak is checked.

[0022] This invention addresses the shortcomings of the prior art and has the following beneficial effects:

[0023] (1) This invention provides an electronic-grade chlorosilane refining and closed-loop safe filling process, which adopts an integrated process flow of distillation column, side stream extraction, fixed bed adsorption and variable temperature regeneration. The distillation column uses the boiling point difference between components to remove light components with large boiling point differences in the system in advance, so that the concentration of boron and phosphorus impurities in the material entering the adsorption column is reduced to a low level. This load distribution strategy allows the adsorption column to only target the residual boron and phosphorus association for deep capture, avoiding the rapid breakthrough caused by the adsorbent directly treating high concentration impurity materials. The distillation pretreatment reduces the inlet impurity load of the adsorption column, effectively extends the breakthrough cycle of the adsorption column, reduces the regeneration frequency accordingly, and increases the continuous operation time of the device. At the same time, the distillation column does not need to use an excessively high reflux ratio to complete the pre-separation task. The heat load of the reboiler and condenser is controlled at a reasonable level, and the equipment size and investment cost are optimized.

[0024] (2) The composite adsorbent of this invention is a mixture of modified X-type molecular sieve and amino-functionalized hydroxylated carbon nanotubes in a specific ratio. The X-type molecular sieve has a regular pore structure, and its pore size matches the dynamic diameter of boron and phosphorus impurity molecules, which can generate a molecular sieving effect. The loaded nickel oxide provides coordination unsaturated metal sites, and the d orbital holes of nickel ions form coordination bonds with the lone pairs of electrons of phosphorus atoms or boron atoms in boron and phosphorus species, thereby achieving chemical adsorption and capture of the associated molecules. The hydroxyl and amino functional groups on the surface of the amino-functionalized carbon nanotubes can form hydrogen bonds with the polar molecules containing boron and phosphorus, providing additional physical adsorption capacity. At the same time, the high thermal conductivity of the carbon nanotubes themselves enables them to quickly conduct heat during adsorption and regeneration, maintaining a uniform temperature distribution in the bed. A synergistic mechanism is formed between the molecular sieve and the carbon nanotubes, with chemical adsorption as the main component, physical adsorption as the auxiliary component, and thermal conduction as the guarantee. The selectivity and adsorption capacity of the adsorbent for boron and phosphorus species are improved compared with single-component adsorbents, the working cycle of the adsorption column is extended, the number of regenerations is reduced, and thus the service life of the adsorbent is improved.

[0025] (3) This invention adopts an operating mode combining low-temperature adsorption and high-temperature variable-temperature regeneration. The adsorption operation is carried out under low-temperature conditions. In the low-temperature environment, the thermal motion speed of boron-phosphorus conjugate molecules slows down, the molecular kinetic energy decreases, and the van der Waals forces and coordination bonds between the active sites on the adsorbent surface and impurity molecules are relatively enhanced, increasing the adsorption driving force. The adsorbent's ability to capture boron-phosphorus species is significantly improved compared to room-temperature operation. During the regeneration stage, high-temperature high-purity hydrogen is introduced as a carrier gas. Utilizing the physicochemical principle that the adsorption capacity decreases with increasing temperature, the adsorbed boron-phosphorus species obtain sufficient desorption activation energy under high-temperature conditions, completely desorbing from the adsorbent surface and being carried out by the carrier gas, thus restoring the active sites of the adsorbent. Low-temperature adsorption ensures high single-pass removal efficiency, while high-temperature regeneration ensures complete recovery of the adsorbent's performance. The alternating cycle of the two allows the adsorbent to maintain a stable working state for a long time, thereby avoiding the problem of gradual deactivation of the adsorbent due to irreversible adsorption and reducing the operating costs caused by frequent adsorbent replacement.

[0026] (4) The present invention adopts a dual-tower or multi-tower alternating operation mode in the adsorption column. After the adsorption of a single tower is saturated, it can be switched online to the regeneration loop for high-temperature purging regeneration. After the regeneration is completed, it is switched back to the adsorption loop to continue working. The adsorption and regeneration states of the two or more towers alternate. The entire system does not need to interrupt the material flow due to adsorbent regeneration, realizing the continuous operation of the production process. This makes the overall process have good operational flexibility and can adapt to the fluctuations of upstream feed flow and impurity concentration. The annual operating time of the device is effectively guaranteed, thereby avoiding the downtime waiting time necessary for adsorbent regeneration in the single-tower operation mode. The production efficiency and equipment utilization rate are improved. Attached Figure Description

[0027] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0028] Figure 1 This is a schematic flowchart of an electronic-grade chlorosilane refining and sealed safety filling process according to the present invention. Detailed Implementation

[0029] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0030] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein. Therefore, the scope of protection of the invention is not limited to the specific embodiments disclosed below.

[0031] It should be noted that, unless otherwise specified, the raw materials, equipment and reagents used in this invention can be purchased from the market or obtained through existing preparation methods.

[0032] In the examples and comparative examples, the raw materials used for preparation are described as follows: trichlorosilane raw material, industrial grade, purity ≥99.5%; 13X type molecular sieve, Si / Al molar ratio of 2.5, specific surface area ≥700 m² 2 / g, pore size 0.8-1.0 nm; multi-walled carbon nanotubes, diameter 10-20 nm, length 5-15 μm, purity ≥95 wt%; Ni(NO3)2·6H2O, analytical grade, purity ≥98.0 wt%; γ-aminopropyltriethoxysilane, analytical grade, purity ≥99.0 wt%; silica sol, SiO2 content 30 wt%; concentrated sulfuric acid, analytical grade, mass fraction 98 wt%; concentrated nitric acid, analytical grade, mass fraction 68 wt%; anhydrous ethanol, analytical grade, purity ≥99.7 wt%; high-purity hydrogen, purity ≥99.9995%, dew point ≤-85 ℃; ethylene glycol, analytical grade, purity ≥99.5 wt%, used to prepare ethylene glycol aqueous solution as a refrigerant for heat exchangers.

[0033] This invention provides an example of adsorbent preparation.

[0034] Preparation Example 1:

[0035] This preparation example provides a method for preparing composite adsorbent A1, including the following steps:

[0036] Preparation of modified X-type molecular sieve: 13X molecular sieve raw powder was placed in a forced-air drying oven and activated at 120 ℃ for 4 h. 100 g of the activated 13X molecular sieve was weighed and set aside. The required amount of Ni(NO3)2·6H2O was calculated based on a loading of 3.5 wt% (calculated as NiO). Specifically, the target loading of NiO was 3.5 g, the molar mass of Ni(NO3)2·6H2O was 290.81 g / mol, the molar mass of NiO was 74.69 g / mol, and the required mass of Ni(NO3)2·6H2O was 3.5 × 290.81 ÷ 74.69 = 13.63 g. 13.63 g of Ni(NO3)2·6H2O was dissolved in water to prepare a solution with a total volume equal to the saturated water absorption volume of the 13X molecular sieve. The activated 13X molecular sieve was immersed in the above-mentioned nickel nitrate aqueous solution and allowed to stand at room temperature for 12 h. Then it was dried at 110 °C for 6 h. The dried product was placed in a muffle furnace and heated to 550 °C at a heating rate of 2 °C / min in air atmosphere and calcined for 4 h to obtain a modified X-type molecular sieve with a NiO loading of 3.5 wt%, labeled as M-1.

[0037] Preparation of amino-functionalized hydroxylated carbon nanotubes: 20 g of multi-walled carbon nanotubes were placed in a round-bottom flask, and 200 mL of a mixed acid solution with a volume ratio of concentrated sulfuric acid to concentrated nitric acid of 3:1 was added. The mixture was ultrasonically treated in a 60 ℃ water bath for 4 h. After ultrasonic treatment, the filtrate was repeatedly washed with water until the pH value of the filtrate was 6-7. The filtrate was then vacuum dried at 80 ℃ for 12 h to obtain hydroxylated carbon nanotubes. The hydroxyl content was determined to be 3.8 mmol / g by titration. 10 g of hydroxylated carbon nanotubes were dispersed in 500 mL of anhydrous ethanol, and 1.0 g of KH-550 was added. The mixture was refluxed and stirred at 70 ℃ for 6 h. After the reaction was completed, the mixture was filtered, washed three times with anhydrous ethanol, and vacuum dried at 60 ℃ to obtain amino-functionalized hydroxylated carbon nanotubes, labeled as C-1.

[0038] Forming of the composite adsorbent: Take 700 g of the modified X-type molecular sieve M-1 and 300 g of amino-functionalized hydroxylated carbon nanotubes C-1, put them into a high-speed mixer, add 500 g of silica sol (of which 150 g of SiO2 solids account for 5 wt% of the total mass of the adsorbent), mix thoroughly for 30 min, and then extrude the mixed material into cylindrical strips with a diameter of 3 mm and a length of 5-10 mm using an extrusion molding machine. Dry the extruded strips at 120 ℃ for 4 h, and then place them in a tube furnace and calcine them at 500 ℃ at 2 ℃ / min under a N2 protective atmosphere for 3 h to obtain the finished composite adsorbent A1.

[0039] Preparation Example 2:

[0040] This preparation example provides a method for preparing composite adsorbent A2.

[0041] The difference between this preparation example and Preparation Example 1 is that the mass ratio of the modified X-type molecular sieve to the amino-functionalized hydroxylated carbon nanotubes is 5:5. Specifically, 500 g of M-1 and 500 g of C-1 were taken, and 500 g of silica sol (150 g of SiO2 solids, accounting for 5 wt% of the total adsorbent mass) was added. The remaining steps and process parameters were completely consistent with Preparation Example 1 to obtain the finished composite adsorbent A2.

[0042] Preparation Example 3:

[0043] This preparation example provides a method for preparing composite adsorbent A3.

[0044] The difference between this preparation example and Preparation Example 1 is that the mass ratio of the modified X-type molecular sieve to the amino-functionalized hydroxylated carbon nanotubes is 9:1. Specifically, 900 g of M-1 and 100 g of C-1 were taken, and 500 g of silica sol (150 g of SiO2 solids, accounting for 5 wt% of the total adsorbent mass) was added. The remaining steps and process parameters were completely consistent with Preparation Example 1 to obtain the finished composite adsorbent A3.

[0045] Preparation Example 4:

[0046] This preparation example provides a method for preparing composite adsorbent A4.

[0047] The difference between this preparation example and Preparation Example 1 is that the NiO loading is adjusted to 1.0 wt%. The required mass of Ni(NO3)2·6H2O is 1.0 × 290.81 ÷ 74.69 = 3.89 g. 3.89 g of Ni(NO3)2·6H2O is dissolved in water to prepare an impregnation solution. The remaining steps are consistent with the preparation method of the modified X-type molecular sieve in Preparation Example 1, resulting in modified X-type molecular sieve M-4 with a NiO loading of 1.0 wt%. In the molding step of the composite adsorbent, 700 g of M-4 and 300 g of C-1 are taken, and the rest is completely consistent with Preparation Example 1, resulting in the finished composite adsorbent A4.

[0048] Preparation Example 5:

[0049] This preparation example provides a method for preparing composite adsorbent A5.

[0050] The difference between this preparation example and Preparation Example 1 is that the NiO loading is adjusted to 10.0 wt%. The required mass of Ni(NO3)2·6H2O is 10.0 × 290.81 ÷ 74.69 = 38.94 g. 38.94 g of Ni(NO3)2·6H2O is dissolved in water to prepare an impregnation solution. The remaining steps are consistent with the preparation method of the modified X-type molecular sieve in Preparation Example 1, resulting in modified X-type molecular sieve M-5 with a NiO loading of 10.0 wt%. In the molding step of the composite adsorbent, 700 g of M-5 and 300 g of C-1 are taken, and the rest is completely consistent with Preparation Example 1, resulting in the finished composite adsorbent A5.

[0051] Preparation Example 6:

[0052] This preparation example provides a method for preparing composite adsorbent A6.

[0053] The difference between this preparation example and Preparation Example 1 is that the carbon nanotubes are not subjected to amino functionalization modification. That is, multi-walled carbon nanotubes are oxidized with mixed acid to obtain hydroxylated carbon nanotubes, which are then directly used in the preparation of the composite adsorbent without the KH-550 reflux modification step. The preparation method of the hydroxylated carbon nanotubes is completely consistent with Preparation Example 1. In the composite adsorbent forming step, 700 g of M-1 and 300 g of unfunctionalized hydroxylated carbon nanotubes are taken, and the rest is completely consistent with Preparation Example 1, to obtain the finished composite adsorbent A6.

[0054] Comparative preparation example 1:

[0055] This preparation example provides a method for preparing the comparative adsorbent D1.

[0056] D1 is unmodified 13X molecular sieve raw powder. After drying the 13X molecular sieve raw powder at 120 °C for 4 h, it is extruded into cylindrical strips with a diameter of 3 mm and a length of 5-10 mm using an extrusion molding machine. The strips are then dried at 120 °C for 4 h and calcined at 500 °C for 3 h (under N2 protective atmosphere) to obtain the comparative adsorbent D1.

[0057] Comparative preparation example 2:

[0058] This preparation example provides a method for preparing the comparative adsorbent D2.

[0059] D2 is a single modified molecular sieve without carbon nanotube components. 1000 g of M-1 was taken and 500 g of silica sol (150 g of SiO2 solids, accounting for 5 wt% of the total adsorbent mass) was added. After mixing thoroughly for 30 min, it was extruded into strips, dried at 120 ℃ for 4 h, and calcined at 500 ℃ for 3 h (under N2 protective atmosphere) to obtain the control adsorbent D2.

[0060] Comparative preparation example 3:

[0061] This preparation example provides a method for preparing the comparative adsorbent D3.

[0062] D3 is a single carbon nanotube adsorbent without molecular sieve components. 1000 g of C-1 was taken and 500 g of silica sol (150 g of SiO2 solids, accounting for 5 wt% of the total adsorbent mass) was added. After mixing thoroughly for 30 min, it was extruded into strips, dried at 120 ℃ for 4 h, and calcined at 500 ℃ for 3 h (under N2 protective atmosphere) to obtain the control adsorbent D3.

[0063] Comparative preparation example 4:

[0064] This preparation example provides a method for preparing the comparative adsorbent D4.

[0065] The difference between this preparation example and Preparation Example 1 is that the mass ratio of modified X-type molecular sieve to amino-functionalized hydroxylated carbon nanotubes is 3:7. Specifically, 300 g of M-1 and 700 g of C-1 were taken, and 500 g of silica sol was added. The rest was exactly the same as in Preparation Example 1, resulting in the comparative adsorbent D4.

[0066] Comparative preparation example 5:

[0067] This preparation example provides a method for preparing the comparative adsorbent D5.

[0068] The difference between this preparation example and Preparation Example 1 is that the mass ratio of modified X-type molecular sieve to amino-functionalized hydroxylated carbon nanotubes is 9.5:0.5. Specifically, 950 g of M-1 and 50 g of C-1 were taken, and 500 g of silica sol was added. The rest was completely consistent with Preparation Example 1 to obtain the comparative adsorbent D5.

[0069] Comparative preparation example 6:

[0070] This preparation example provides a method for preparing the comparative adsorbent D6.

[0071] D6 is a commercially available activated carbon adsorbent, model AC-1, purchased from Fujian Xinsen Carbon Industry Co., Ltd., with a specific surface area of ​​1100 m². 2 / g, iodine adsorption value is 1000 mg / g.

[0072] This invention provides a process for refining and sealing-safe filling of electronic-grade chlorosilanes.

[0073] Example 1:

[0074] like Figure 1 As shown, this embodiment provides a process for refining and sealing-safe filling of electronic-grade chlorosilanes, including the following steps:

[0075] Distillation separation step: Industrial-grade trichlorosilane feedstock is continuously fed into the distillation column at a feed flow rate of 100 kg / h. The distillation column is a high-efficiency packed column, filled with structured packing material with a specific surface area of ​​500 m². 2 / m 3 The distillation column has 30 theoretical plates. The operating pressure is 0.35 MPa (absolute), the reflux ratio is 8:1, and the top temperature is 33 °C. A fraction containing light components such as SiCl4 and SiH2Cl2 is collected from the top. The bottom temperature is 88 °C, and a fraction containing heavy components such as polysiloxanes and metal chlorides is collected from the bottom. A side stream outlet is located at the 20th theoretical plate (4th plate above the feed plate). This side stream collects trichlorosilane rich in boron and phosphorus impurities, at a rate of 6.5 wt% of the total feed.

[0076] Pre-cooling and adsorption steps: The side-stream sampled material enters a shell-and-tube heat exchanger, where it is pre-cooled to -15 °C using an ethylene glycol aqueous solution as the coolant. It is then fed into a fixed-bed adsorption column filled with composite adsorbent A1 for low-temperature adsorption. The height-to-diameter ratio of the adsorption column is 5:1, and the volume of adsorbent packed in a single column is 0.6 m³. 3 The adsorption column operates at a pressure of 0.32 MPa and a material space velocity of 0.8 h⁻¹. -1 The adsorption temperature is -15 ℃, and the adsorbed and purified trichlorosilane material is returned to the reflux system of the distillation column.

[0077] Regeneration Steps: The adsorption column employs a dual-tower alternating operation, with a single-tower adsorption cycle of 72 hours. After adsorption saturation, the adsorption column is switched to the regeneration system, using high-purity hydrogen as the regeneration carrier gas for temperature-variable purging regeneration at a flow rate of 0.4 m³ / s. 3 The regeneration process involves a regeneration rate of / h·kg adsorbent, a regeneration temperature of 165 ℃, a regeneration pressure of 0.20 MPa, a heating phase of 2.5 h, a constant-temperature purging phase of 1.5 h, and a cooling phase of 2.0 h, for a total regeneration cycle of 6.0 h. After regeneration, the system switches back to adsorption mode to achieve continuous production.

[0078] Closed-loop safety filling process: After purification, the trichlorosilane product is filtered through a precision filter under inert gas protection and then filled into stainless steel containers that have undergone high-purity inert gas purging and vacuum treatment using a closed-loop filling system. The filling volume is controlled by a mass flow meter throughout the filling process. The filling system is equipped with pressure interlock shut-off and leak detection devices. After filling, the container valves are sealed and leak checked. The entire process is carried out within a closed system, with high-purity nitrogen protection used throughout the distillation, adsorption, and filling processes.

[0079] Example 2:

[0080] This embodiment is basically the same as Embodiment 1, except that: the reflux ratio of the distillation column is 6:1, the top temperature of the column is 36℃, and the bottom temperature of the column is 95℃; the side stream is located at the 15th theoretical plate of the distillation column, and the side stream accounts for 3.0 wt% of the total feed; the adsorption column is filled with composite adsorbent A2; the remaining steps and process parameters are completely consistent with Embodiment 1.

[0081] Example 3:

[0082] This embodiment is basically the same as Embodiment 1, except that: the reflux ratio of the distillation column is 12:1, the top temperature is 30℃, and the bottom temperature is 80℃; the side stream is located at the 25th theoretical plate of the distillation column, and the side stream amount accounts for 10.0 wt% of the total feed; the adsorption column is filled with composite adsorbent A3; the remaining steps and process parameters are completely consistent with Embodiment 1.

[0083] Example 4:

[0084] This embodiment is basically the same as Embodiment 1, except that: the material collected from the side stream is pre-cooled to -10°C by a heat exchanger, the adsorption column operating pressure is 0.25 MPa, and the material space velocity is 0.3 h⁻¹. -1 The adsorption temperature was -10 ℃; the adsorption column was filled with composite adsorbent A4; the remaining steps and process parameters were completely consistent with those in Example 1.

[0085] Example 5:

[0086] This embodiment is basically the same as Embodiment 1, except that: the side-stream sampled material is pre-cooled to -20°C by a heat exchanger, the adsorption column operating pressure is 0.35 MPa, and the material space velocity is 1.5 h⁻¹. -1 The adsorption temperature was -20 ℃; the adsorption column was filled with composite adsorbent A5; the remaining steps and process parameters were completely consistent with those in Example 1.

[0087] Example 6:

[0088] This embodiment is basically the same as Embodiment 1, except that the regeneration temperature is 150 ℃ and the regeneration carrier gas flow rate is 0.2 m³ / s. 3 The regeneration cycle is 8.5 h, with a heating phase of 3.0 h, a constant temperature purging phase of 2.5 h, and a cooling phase of 3.0 h. The remaining steps and process parameters are completely consistent with those in Example 1.

[0089] Example 7:

[0090] This embodiment is basically the same as Embodiment 1, except that the regeneration temperature is 180 ℃ and the regeneration carrier gas flow rate is 0.8 m³. 3 The regeneration cycle is 3.0 h, with a heating phase of 1.0 h, a constant temperature purging phase of 1.0 h, and a cooling phase of 1.0 h. The remaining steps and process parameters are completely consistent with those in Example 1.

[0091] Example 8:

[0092] This embodiment is basically the same as Embodiment 1, except that the adsorption cycle of a single tower is 96 hours; the remaining steps and process parameters are completely consistent with Embodiment 1.

[0093] Comparative Example 1:

[0094] This comparative example is basically the same as Example 1, except that the adsorption column is filled with comparative adsorbent D1, which is unmodified 13X molecular sieve powder; the remaining steps and process parameters are completely consistent with Example 1.

[0095] Comparative Example 2:

[0096] This comparative example is basically the same as Example 1, except that the adsorption column is filled with comparative adsorbent D2, which is a single modified molecular sieve without carbon nanotube components; the remaining steps and process parameters are completely consistent with Example 1.

[0097] Comparative Example 3:

[0098] This comparative example is basically the same as Example 1, except that the adsorption column is filled with comparative adsorbent D3, which is a single carbon nanotube adsorbent without molecular sieve components; the remaining steps and process parameters are completely consistent with Example 1.

[0099] Comparative Example 4:

[0100] This comparative example is basically the same as Example 1, except that the adsorption column is filled with comparative adsorbent D4, i.e., the mass ratio of modified X-type molecular sieve to amino-functionalized hydroxylated carbon nanotubes is 3:7; the remaining steps and process parameters are completely consistent with Example 1.

[0101] Comparative Example 5:

[0102] This comparative example is basically the same as Example 1, except that: the adsorption column is filled with comparative adsorbent D5, that is, the mass ratio of modified X-type molecular sieve to amino-functionalized hydroxylated carbon nanotubes is 9.5:0.5; the remaining steps and process parameters are completely consistent with Example 1.

[0103] Comparative Example 6:

[0104] This comparative example is basically the same as Example 1, except that the adsorption column is filled with comparative adsorbent D6, i.e., commercially available activated carbon adsorbent; the remaining steps and process parameters are completely consistent with Example 1.

[0105] Comparative Example 7:

[0106] This comparative example is basically the same as Example 1, except that: the material collected from the side stream is not pre-cooled by a heat exchanger, but directly enters the adsorption column for adsorption at the side stream collection temperature (about 29 ℃), that is, the adsorption temperature is 29 ℃; the remaining steps and process parameters are completely consistent with Example 1.

[0107] Comparative Example 8:

[0108] This comparative example is basically the same as Example 1, except that the regeneration temperature is 120 ℃; the remaining steps and process parameters are completely consistent with Example 1.

[0109] Comparative Example 9:

[0110] This comparative example is basically the same as Example 1, except that the reflux ratio of the distillation column is 4:1; the remaining steps and process parameters are completely consistent with Example 1.

[0111] Performance testing: The specific surface area and crushing strength of the adsorbents in Example 1 and Comparative Examples 1-6 were tested to verify the synergistic effect of molecular sieve and carbon nanotubes in the composite adsorbent and the influence of NiO loading on the structure and performance of the adsorbent.

[0112] Specific surface area testing: The nitrogen adsorption-desorption method was used, and the specific surface area and porosity were measured using a specific surface area and porosity analyzer. Before testing, the sample was degassed under vacuum at 300 °C for 6 h. Using N2 as the adsorbate, the adsorption-desorption isotherm was measured at -196 °C liquid nitrogen temperature, and the specific surface area was calculated using the BET method.

[0113] Crushing strength test: The test was conducted according to HG / T 2783-2020 "Test Method for Crushing Resistance of Molecular Sieve". Strip samples with a length of 5-10 mm were taken and tested using an intelligent particle strength tester. 30 particles were measured in parallel for each sample, and the arithmetic mean was taken. The result is expressed in N / cm.

[0114] Adsorption capacity test: Dynamic adsorption capacity tests were conducted on the adsorbents of Example 1 and Comparative Examples 1-7. A simulated trichlorosilane feed solution with a B concentration of 50 ppb (introduced as BCl3) and a P concentration of 50 ppb (introduced as PCl3) was prepared. The adsorbent was crushed and sieved to 20-40 mesh, and filled into a stainless steel adsorption tube with an inner diameter of 10 mm, to a filling height of 100 mm. After pre-cooling the simulated feed solution to the corresponding adsorption temperature, the adsorption capacity was tested at 0.8 h. -1 The liquid hourly space velocity (LHSV) passes through the adsorption bed, and the B and P concentrations at the outlet are monitored online. Breakthrough is defined as when the outlet B or P concentration reaches 10% of the inlet concentration, and the breakthrough adsorption capacity is calculated.

[0115] Product purity testing: The purified trichlorosilane products from each example and comparative example were collected, and the B and P contents were determined by inductively coupled plasma mass spectrometry (ICP-MS). Samples were digested with nitric acid and then diluted to a final volume. Quantification was performed using a standard curve method, with a detection limit of 0.01 ppb.

[0116] Regeneration performance test: For the adsorption columns of each example and comparative example, the adsorption capacity was tested again after completing one full adsorption-regeneration cycle. The retention rate of the adsorption capacity of the adsorbent after multiple cycles was used to evaluate the regeneration effect. The regeneration efficiency was calculated according to the formula (regenerated adsorption capacity ÷ initial adsorption capacity) × 100%.

[0117] Table 1 lists the test results of the adsorbent structure properties and adsorption capacity of Example 1 and Comparative Examples 1-6.

[0118] Table 1: Structural properties and adsorption capacity of different adsorbents

[0119] project <![CDATA[Specific surface area / m 2 ·g -1 > <![CDATA[Crushing strength / N·cm -1 > <![CDATA[B Dynamic Adsorption Capacity / mg·g -1 > <![CDATA[P Dynamic Adsorption Capacity / mg·g -1 > Example 1 682 62 2.85 2.24 Comparative Example 1 705 48 1.12 0.85 Comparative Example 2 635 55 2.01 1.56 Comparative Example 3 210 18 0.98 0.72 Comparative Example 4 620 38 1.85 1.42 Comparative Example 5 695 65 2.12 1.63 Comparative Example 6 1100 42 0.61 0.45

[0120] As can be seen from Table 1, the specific surface area of ​​the composite adsorbent in Example 1 is 682 m². 2 The dynamic adsorption capacity of B was 2.85 mg / g, and the dynamic adsorption capacity of P was 2.24 mg / g. Comparative Example 1 was an unmodified 13X molecular sieve, although its specific surface area was as high as 705 m² / g. 2However, its B / P adsorption capacity was only 1.12 mg / g and 0.85 mg / g, far lower than that of Example 1. This is because the 13X molecular sieve without NiO loading relies solely on physical adsorption and molecular sieving effects to capture boron and phosphorus species, lacking the chemisorption provided by coordinating unsaturated metal sites, thus limiting its ability to capture associated molecules. Comparative Example 2 is a single modified molecular sieve without carbon nanotubes, whose specific surface area decreased to 635 m². 2 The adsorption capacities were 2.01 mg / g and 1.56 mg / g, respectively, which were significantly lower than those in Example 1. This is because the lack of physical adsorption capacity replenishment and thermal conduction channels from the carbon nanotube component reduced the utilization rate of adsorption sites. Comparative Example 3 was a single carbon nanotube adsorbent without molecular sieves, with a specific surface area of ​​only 210 m². 2 The adsorption capacities were only 0.98 mg / g and 0.72 mg / g, indicating that carbon nanotubes alone have limited physical adsorption capacity and lack selective chemisorption sites like molecular sieves. In Comparative Example 4, the molecular sieve to carbon nanotube mass ratio was 3:7. The excessively high carbon nanotube ratio resulted in an adsorbent crushing strength of only 38 N / cm, indicating that excessive carbon nanotubes weakened the supporting role of the molecular sieve framework, leading to insufficient mechanical strength of the adsorbent. In Comparative Example 5, the mass ratio was 9.5:0.5, with an excessively low carbon nanotube ratio. Its adsorption capacities were 2.12 mg / g and 1.63 mg / g, lower than in Example 1. This is because insufficient carbon nanotube content leads to inadequate thermal conduction channels and insufficient physical adsorption capacity replenishment. Comparative Example 6 used commercially available activated carbon, although its specific surface area was as high as 1100 m². 2 However, its adsorption capacity for B / P is only 0.61 mg / g and 0.45 mg / g. This is because the activated carbon surface lacks functional groups and coordination sites with selective affinity for boron-phosphorus composites, and its high specific surface area advantage has not been effectively converted into adsorption capacity for target impurities.

[0121] The above results indicate that only when modified X-type molecular sieves are combined with amino-functionalized hydroxylated carbon nanotubes in an appropriate ratio can the synergistic effect of the molecular sieve's chemical adsorption selectivity, the carbon nanotubes' physical adsorption capacity supplementation, and the thermal conductivity function enable the adsorbent to achieve excellent adsorption performance while maintaining high mechanical strength.

[0122] Table 2 lists the B / P content test results of the refined products of each embodiment and comparative example. It should be noted that the purity test results of the products of comparative examples 1-6 are all listed in Table 2 for consistent comparison.

[0123] Table 2: Purity and Adsorption Performance of Products from Each Example and Comparative Example

[0124] project Product B content / ppb Product P content / ppb Adsorbent breakthrough time / h Adsorption capacity retention rate after regeneration / % Example 1 0.04 0.06 75 98.2 Example 2 0.06 0.08 68 97.5 Example 3 0.03 0.05 80 98.0 Example 4 0.05 0.07 62 97.0 Example 5 0.04 0.06 78 98.5 Example 6 0.05 0.07 72 95.2 Example 7 0.04 0.06 73 98.8 Example 8 0.04 0.06 98 97.6 Comparative Example 1 2.50 3.20 18 86.0 Comparative Example 2 0.85 1.10 35 90.2 Comparative Example 3 4.50 5.80 10 82.5 Comparative Example 4 1.20 1.60 28 88.5 Comparative Example 5 0.72 0.95 42 92.0 Comparative Example 6 8.50 10.20 6 70.0 Comparative Example 7 0.85 1.05 38 90.5 Comparative Example 8 0.35 0.48 45 72.5 Comparative Example 9 0.45 0.60 50 93.0

[0125] In terms of product purity, the B content of Examples 1-8 is ≤0.06 ppb and the P content is ≤0.08 ppb, which meets the purity requirements for electronic-grade polycrystalline silicon precursors in processes of 3nm and below. The products of Comparative Examples 1-7 have a B content ≥0.72 ppb and a P content ≥0.95 ppb, which fails to meet the requirements of advanced processes.

[0126] Comparative Example 1 had B / P ratios of 2.50 ppb and 3.20 ppb, due to the use of unmodified 13X molecular sieves, which lack chemisorption active sites. Comparative Example 3 used single carbon nanotubes, resulting in product B / P ratios as high as 4.50 ppb and 5.80 ppb, because carbon nanotubes alone only provide limited physical adsorption capacity and lack the selective sieving effect and chemisorption function of molecular sieves. Comparative Example 4 had a molecular sieve to carbon nanotube mass ratio of 3:7. Excessive carbon nanotubes led to reduced adsorbent crushing strength, decreased packing density, and reduced effective adsorption site volume concentration, resulting in product B / P ratios of 1.20 ppb and 1.60 ppb. Comparative Example 5 had a mass ratio of 9.5:0.5. Insufficient carbon nanotube content resulted in inadequate heat conduction channels, preventing timely dissipation of adsorption exothermics and causing localized temperature increases in the bed, resulting in product B / P ratios of 0.72 ppb and 0.95 ppb. Comparative Example 6 used commercially available activated carbon, with B / P ratios of 8.50 ppb and 10.20 ppb, demonstrating that conventional activated carbon has virtually no selective adsorption capacity for boron-phosphorus conjugates in the trichlorosilane system. Comparative Example 7 showed adsorption temperatures of 29 ℃ and B / P ratios of 0.85 ppb and 1.05 ppb, because at room temperature, the molecular thermal motion of boron-phosphorus conjugates is relatively rapid, resulting in relatively weak van der Waals forces and coordination bonds between the active sites on the adsorbent surface and impurity molecules, leading to insufficient adsorption driving force.

[0127] Regarding the breakthrough time of the adsorbent, the breakthrough time of Example 1 was 75 h, which was more than four times that of Comparative Example 1 (18 h). This is because the NiO loading in the composite adsorbent provides coordination unsaturated sites with strong chemisorption of boron-phosphorus conjugates, and the physical adsorption capacity and thermal conductivity of the carbon nanotube component further extend the effective working cycle of the adsorbent. Comparative Example 8 had a regeneration temperature of 120 °C. Although the purity of the fresh adsorbent was acceptable (B 0.35 ppb, P 0.48 ppb), the adsorption capacity retention rate after regeneration was only 72.5%, and the breakthrough time was only 45 h. This was because the regeneration temperature was too low, causing the adsorbed boron-phosphorus species to not obtain sufficient desorption activation energy, resulting in incomplete desorption and partial occupation of active sites. Comparative Example 9 had a distillation reflux ratio of 4:1, which resulted in insufficient pre-separation by distillation, leading to an increased B / P impurity concentration entering the adsorption column. The breakthrough time was 50 h, and the B / P content of the product was 0.45 ppb and 0.60 ppb, respectively.

[0128] As shown in Table 2, the adsorption capacity retention rates after regeneration in Examples 1-8 all remained above 95%, indicating that the active sites of the adsorbent can be efficiently regenerated under the preferred process conditions. Example 7 showed the highest retention rate (98.8%) after regeneration because the regeneration temperature of 180 °C provided a higher desorption activation energy for the boron-phosphorus species, resulting in more thorough desorption, but also increasing regeneration energy consumption. Comparative Example 8 showed a retention rate of only 72.5% after regeneration, demonstrating insufficient desorption at regeneration temperatures below 150 °C. The activated carbon retention rate in Comparative Example 6 was only 70.0% after regeneration because the pore structure of the activated carbon was gradually destroyed during high-temperature regeneration due to coking or sintering.

[0129] The experimental data above demonstrate that this invention, through load distribution of pre-separation by distillation and low-temperature adsorption, complementary adsorption-thermal conduction functions of molecular sieves and carbon nanotubes, and synergistic thermal cycling of low-temperature adsorption and high-temperature variable-temperature regeneration, achieves highly efficient and deep removal of boron and phosphorus impurities from hundreds of ppb levels to ≤0.06 ppb levels. The adsorbent breakthrough time is ≥72 h, the adsorption capacity retention rate after regeneration is ≥95%, and the adsorbent replacement cycle is significantly extended. Compared with conventional multi-stage distillation and single adsorption methods, this invention has significant advantages in product quality, adsorbent lifespan, and overall energy consumption.

[0130] The above description is based on the preferred embodiments of the present invention. It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered exemplary and non-limiting in all respects. The scope of the invention is defined by the appended claims rather than the foregoing description, and all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.

[0131] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A process for refining and sealing-safe filling electronic-grade chlorosilanes, characterized in that, Includes the following steps: Trichlorosilane feedstock is continuously fed into a distillation column for distillation separation. The light component is collected from the top of the column, the heavy component is collected from the bottom of the column, and the trichlorosilane material rich in boron and phosphorus impurities is collected from the side stream above the feed plate of the distillation column. The material collected from the side stream is pre-cooled by a heat exchanger and then fed into a fixed-bed adsorption column filled with a composite adsorbent for low-temperature adsorption to remove boron and phosphorus impurities. The composite adsorbent includes a modified X-type molecular sieve and hydroxylated multi-walled carbon nanotubes. The modified X-type molecular sieve is an X-type molecular sieve loaded with transition metal oxides. The adsorption-purified trichlorosilane material is returned to the reflux system of the distillation column or collected as a product. After adsorption saturation, the adsorption column is switched to the regeneration system. High-purity carrier gas is used for temperature-variable purging and regeneration under high temperature conditions. After regeneration, it is switched back to the adsorption state. The adsorption column adopts dual-tower or multi-tower alternating operation to achieve continuous production. The process is carried out in a closed system, and inert gas protection is used throughout the distillation, adsorption and filling processes.

2. The electronic-grade chlorosilane refining and sealed safety filling process according to claim 1, characterized in that, In the composite adsorbent, the mass ratio of modified X-type molecular sieve to hydroxylated multi-walled carbon nanotubes is 5-9:1-5, and the loading of transition metal oxide in the modified X-type molecular sieve is 1-10 wt%, wherein the transition metal oxide is selected from one of NiO, CuO, and ZnO.

3. The electronic-grade chlorosilane refining and sealed safety filling process according to claim 2, characterized in that, The modified X-type molecular sieve matrix is ​​13X type molecular sieve with a Si / Al molar ratio of 2.0-3.0 and a specific surface area ≥600 m². 2 / g, with a pore size of 0.7-1.2 nm; the modified X-type molecular sieve, after being impregnated with a transition metal oxide in equal volume, is calcined at 400-600℃ for 2-6 h, and its specific surface area is ≥600 m². 2 / g.

4. The electronic-grade chlorosilane refining and sealed safety filling process according to claim 2, characterized in that, The hydroxylated multi-walled carbon nanotubes are obtained by oxidation of multi-walled carbon nanotubes with mixed acid, and the hydroxyl content is 2.0-5.0 mmol / g. The hydroxylated multi-walled carbon nanotubes are further modified with amino functionalization by a silane coupling agent, the silane coupling agent being γ-aminopropyltriethoxysilane, and the amount used is 5-20% of the mass of the carbon nanotubes.

5. The electronic-grade chlorosilane refining and sealed safety filling process according to claim 1, characterized in that, The method for forming the composite adsorbent is as follows: after mixing modified X-type molecular sieve and hydroxylated multi-walled carbon nanotubes, a binder is added, and the mixture is mixed, extruded, dried, and calcined to obtain the finished adsorbent; the binder is one of silica sol and alumina sol; based on solids, the amount of binder is 3-10% of the total mass of the adsorbent, the drying temperature is 80-150 ℃, the calcination temperature is 400-600 ℃, and the calcination atmosphere is an inert atmosphere.

6. The electronic-grade chlorosilane refining and sealed safety filling process according to claim 1, characterized in that, The distillation column has ≥30 theoretical plates, operates at a pressure of 0.30-0.40 MPa, has a reflux ratio of 6-12:1, a top temperature of 30-36 ℃, and a bottom temperature of 80-95 ℃. The side stream is located at the 15th-25th theoretical plate of the distillation column, and the side stream amount accounts for 3-10 wt% of the total feed.

7. The electronic-grade chlorosilane refining and sealed safety filling process according to claim 1, characterized in that, The side-stream sampled material is pre-cooled to -20°C to -10°C via a heat exchanger before entering the adsorption column; the operating pressure of the adsorption column is 0.25-0.35 MPa, and the material space velocity is 0.3-1.5 h⁻¹. -1 The adsorption temperature is -20 ℃ to -10 ℃.

8. The electronic-grade chlorosilane refining and sealed safety filling process according to claim 1, characterized in that, In the regeneration system, the regeneration carrier gas is hydrogen, and the regeneration carrier gas flow rate is 0.2-0.8 m³ / s. 3 The regeneration temperature is 150-180 ℃, and the regeneration pressure is 0.10-0.30 MPa. The heating stage of the variable temperature purge regeneration is 1-3 h, the constant temperature purge stage is 1-2.5 h, the cooling stage is 1-3 h, and the total regeneration cycle is 4-8 h.

9. The electronic-grade chlorosilane refining and sealed safety filling process according to claim 1, characterized in that, The single-tower adsorption cycle is 48-96 h, the height-to-diameter ratio of the adsorption column is 3-8:1, and the specific surface area of ​​the composite adsorbent packed inside the adsorption column is ≥600 m². 2 / g, crushing strength ≥50 N / cm, bulk density 0.6-0.8 g / cm³ 3 The adsorbent has an adsorption capacity of ≥2.0 mg / g for boron and ≥1.8 mg / g for phosphorus under dynamic conditions.

10. The electronic-grade chlorosilane refining and hermetically sealed safety filling process according to any one of claims 1, characterized in that, The refined trichlorosilane product produced by the process has a boron content ≤0.08 ppb and a phosphorus content ≤0.10 ppb. The closed-loop safe filling process includes: filtering the refined trichlorosilane product through a precision filter under inert gas protection, and then filling it into a stainless steel container that has been purged with high-purity inert gas and vacuum treated using a closed-loop filling system. The filling volume is controlled by a mass flow meter throughout the filling process. The filling system is equipped with a pressure interlock shut-off and leakage detection device. After filling, the container valve is sealed and leak is checked.